Influenza B virus non-structural protein 1 counteracts ISG15 antiviral activity by sequestering ISGylated viral proteins - Chen Zhao (Nature Portfolio, 2016)
The ubiquitin-like protein ISG15 can be covalently linked to cellular and viral proteins, but the consequences of this ‘ISGylation’ remain largely unknown. Here, Zhao et al.show that ISGylation of the influenza B virus nucleoprotein inhibits formation of a functional viral replication complex.